Perceiving violence against healthcare workers in a child and adolescent emergency psychiatric ward in Hungary: a qualitative pilot study - Sófi, Gyula; Törő, Krisztina; Csikós, Gábor; Fliegauf, Gergely (Frontiers in Psychology, 2023)
Aim: Psychiatry is a challenging setting that requires extraordinary effort from the staff. Healthcare workers in the field of psychiatry face substantial levels of violence, making the identification of abuse risk factors a social concern. Both the conduct of the children and their relatives can pose potential harm. Our study delved into the criminological and psychiatric factors underlying violence against healthcare workers. Methodology: We used qualitative, semi-structured, self-developed, online questionnaire involving 21 respondents. The participants were representing the staff composition of our department. The data set was coded in two phases using a multi-stage content analysis method. The results were compared with Hungarian and international literature. Findings: Among the participants, 52% reported no instances of physical abuse. The most prevalent form of perceived non-contact abuse was threats, accounting for 38% of reported cases. The identified risk factors for abuse included the child's psychiatric disorder, communication issues, parental behavior, and low socio-economic status. Psychological trauma was identified as the most severe consequence. The respondents' opinion indicated that the most common cause of violence (52%) was attributed to the child's mental disorder. Workers primarily deal with abuse through negative emotions, with 76% of them reporting feelings of victimization. Additionally, 43% believed that abuse cannot be avoided, while 19% emphasized the significance of worker competence. Value: Our research can help to identify risk factors in child psychiatry wards and provide guidance for developing effective responses to violence against healthcare workers in Hungary, especially at our ward.